ASSESSMENT OF EXISTING AGROFORESTRY PRACTICES IN WEST HARARGHE ZONE OF OROMIA REGION, ETHIOPIA - Diriba, Alemayehu; Dekeba, Shimelis; Gizaw, Wasihun (International Journal of Research -GRANTHAALAYAH, 2022)
A study was conducted in west Hararghe zone, on three districts, in six peasant associations with the intention to identify and assess potentials, constraints, opportunities and farmers’ perception on the existing agro-forestry practices of the study areas. The study was multistage sampling methods in which 121 households were selected using random sampling technique. Qualitative data generated by conducting household survey interviews, focus group discussions, key informant interview, and direct field observations in order to fit intention of the study. The collected Data was manipulated using suitable analytical software packages (SPSS, V.20) to calculate percentage and frequency of events through descriptive statistics. Based on the respondents idea across the districts, an average value of home garden agroforestry practices with 86% increasing and 11.5% decreasing and 2.5% no change trends were observed; while alley cropping of agroforestry practice during the past ten years ago with 89.3% increasing and 10.7% decreasing trend was observed (Table 4). Almost all in both Hararghe zones; alley cropping system is the most familiar than other existing agroforestry practices. For instance; an average value across the districts, Kchat plantation in alley cropping practice during the past ten years ago with 97.5% increasing and 2.5% decreasing trend was recorded (Table 4). In the result, the three top and the highest percentage observation of woody species have been retaining and planting in farmland across districts with the specific uses were Catha Edulis with (64.2%), Coffea with (49.9%) and Cordia Africana with (36.7%) could be observed (Table 2). The three top constraints of agroforestry practices were shortage of farm land with (43.8%), lack of understanding with (24.8%) and nutrient competition with (20.7%) observed. Basically, agroforestry practices needs optimum farm land size with related extent in order to compensate the observed constraints. On the contrary, the three top opportunities of agroforestry practices were Multipurpose Utilities with (26.1%), provision of shading with (14.3%) and Climate Balance with (6.7%) observed .It was also found that multipurpose trees shrubs play various traditional roles to local community. Generally; retention and planting of trees/shrubs in farm lands are used for fuel, construction, food, medicine, folder, and aesthetic value, shading values, windbreak, soil conservation and soil fertility improvement, bee forage and other uses in advance.